Virtual Aggregation Using SDN - Skoldstrom, Pontus; Chial Sanchez, Belgis (European Workshop on Software Defined Networking (Print), 2013)
We describe the design and implementation of a system for performing Virtual Aggregation, a method for dividing and spreading a forwarding table over multiple forwarding elements, in an SDN/OpenFlow network. The primary use-case for this method is to alleviate the scalability problems caused by a rapidly growing routing table in the Default-Free Zone (i.e. the BGP routers on the Internet), secondly it could be extended to support OpenFlow network abstractions. The design provides a scalable system for quickly dividing and distributing a forwarding table in an SDN environment running NOX and OpenFlow 1.1. After evaluating the system we conclude that our design is fast, scalable, and extensible.